Conversion of rubber seed oil to biodiesel using continuous ultrasonic reactor - Trinh, H. (Elsevier, 2020)
As an intensification method, the ultrasonic technique can significantly enhance the homogenization of reactants, thus, it has been used in biodiesel production to obtain a more efficient process. Rubber seed oil is a promising nonedible oil source for biodiesel production, however, its main drawback is its high free fatty acid (FFA) content. Esterification pretreatment of FFA is required to reduce the FFA content to less than 1. In the next step of base transesterification, the triglyceride of oil is converted into methyl esters. This chapter focuses on tests conducted using a continuous ultrasonic reactor in order to evaluate its potential up-scaling for its application in biodiesel production. In this study, experiments were carried out in a continuous ultrasonic reactor. The results revealed a faster approach and more energy efficiency in the continuous reactor compared to the batch reactor. In the continuous reactor, acid esterification and base transesterification were completed in 3.5 and 2.3min with energy consumptions of 0.07 and 0.04kJ/mL, respectively. Â© 2020 Elsevier Inc. All rights reserved.